2000
DOI: 10.3758/bf03201243
|View full text |Cite
|
Sign up to set email alerts
|

Modality differences in short-term memory for rhythms

Abstract: Prior research has established that performance in short-term memory tasks using auditory rhythmic stimuli is frequently superior to that in tasks usingvisual stimuli, In fiveexperiments, the reasons for this were explored further. In a same-different task, pairs of brief rhythms were presented in which each rhythm was visual or auditory, resulting in two same-modality conditions and two cross-modality conditions. Three different rates of presentation were used. The results supported the temporal advantage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
67
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 18 publications
17
67
1
Order By: Relevance
“…The items presented on memory lists and probe sequences were the digits 1-9, the digits being presented auditorily to participants. Although the evidence for a modality effect in memory for timing is ambiguous, the partial evidence in favor of an auditory superiority effect led us to use auditory presentation (see, e.g., Collier & Logan, 2000;Glenberg & Jona, 1991;Glenberg, Mann, Altman, Forman, & Procise, 1989;Glenberg & Swanson, 1986; but see Schab & Crowder, 1989;Watkins et al, 1992). The spoken numbers were recorded from a male speaker with a neutral English accent, and digitised for storage on computer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The items presented on memory lists and probe sequences were the digits 1-9, the digits being presented auditorily to participants. Although the evidence for a modality effect in memory for timing is ambiguous, the partial evidence in favor of an auditory superiority effect led us to use auditory presentation (see, e.g., Collier & Logan, 2000;Glenberg & Jona, 1991;Glenberg, Mann, Altman, Forman, & Procise, 1989;Glenberg & Swanson, 1986; but see Schab & Crowder, 1989;Watkins et al, 1992). The spoken numbers were recorded from a male speaker with a neutral English accent, and digitised for storage on computer.…”
Section: Methodsmentioning
confidence: 99%
“…This paper reports and experiment and some model simulations that place constraints on theories of the relationship between timing and order in short-term memory. Participants were presented with list items and asked to pay attention to the order of the items, and their timing; after presentation of list items the participants were instructed to perform a recognition task on the basis of the order of items (i.e., serial recognition), or their timing (i.e., temporal recognition; see Collier & Logan, 2000;Ross & Houtsma, 1994). Assuming a common temporal dimension for timing and order memory, the experiment provides conditions favorable for observing TIEs in serial order memory by explicitly requiring that participants attend to the timing of items.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From this perspective, visual stimuli can evoke activation in auditory association cortex, while auditory stimuli may not evoke a similar response in visual cortex (but, see McIntosh et al, 1998). Moreover, it has been shown that visually presented rhythmic signals are encoded by an auditory code in the brain (Collier and Logan, 2000;Guttman et al, 2005; but, see Grahn et al, 2011). Such an asymmetry in cross-sensory representations might help to explain our asymmetry in the crossmodal transfer of temporal recalibration: the rhythmic visual component of a motor-visual adaptor pair might echo into the auditory modality and induce a motor-"auditory" TRE which then affects the motor-auditory test.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, studies of temporal pattern and rhythm discrimination also reveal modality differences (e.g., Collier & Logan, 2000;Garner & Gottwald, 1968;Glenberg & Jona, 1991;Handel & Buffardi, 1969;Manning, Pasquali, & Smith, 1975;Rubinstein & Gruenberg, 1971). When presented with rhythmic patterns of flashing lights or auditory stimuli, participants were much better at discriminating auditory as opposed to visual patterns (Rubinstein & Gruenberg, 1971).…”
Section: Modality Constraintsmentioning
confidence: 99%